PENGEMBANGAN INSTRUMEN KOMPETENSI PERSONAL MAHASISWA BERBASIS APLIKASI MACROMEDIA FLASH - Andi Wibowo; Nurul Lail Rosyidatul Mu’ammaroh; Wuli Oktiningrum; Adzimatnur Muslihasari; Dyah Ayu Pramoda Wardhani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Personal competence is a person's competence to understand the strengths and weaknesses of oneself and how to interact and interact with others. Personal competence includes interpersonal intelligence and intrapersonal intelligence. This study aims to produce valid and reliable personal competence instruments to map student’s personal competencies in Computer Asisted Test (CAT) using Macromedia Flash software. This mapping aims to optimize student academic guidance activities to reduce the dropout rate. This study adapted the Borg & Gall model. The sampling technique was using a random sampling. The subjects were the students of PGSD. Data collection techniques used were interviews, questionnaires, and tests. The data analysis technique were a four scale score conversion and SPSS Statistics 23. The results are personal competence instruments that is valid and reliable. The results of the content and construct validity of the material and media experts obtained an A with a very good category. The results of empirical validity show that there are 27 valid question items (r count> r table) and 3 invalid question items (r count <r table). The results of the reliability showed that the instrument was reliable in good categories (alfa cronbach value=0,6).